Hegel's Defence of Constitutional Monarchy - Feseha, Markos (Revista Eletrônica Estudos Hegelianos, 2023)
In the Philosophy of Right, Hegel defends the constitutional monarchy as a key element of political sovereignty. Most commentators, however, argue that a rational government requires that the decision power of the monarchy be very limited. Accordingly, scholars such as M.O. Hardimon, Klaus Vieweg, Z.A. Pelczynski and Thom Brooks ignore that, for Hegel, the decision power of the monarchy is crucial to overcome the limits of liberal conceptions of political sovereignty. These liberal scholars, it seems to me, are influenced by Montesquieu’s conception of the division of powers. Yet Hegel rightly argues that while Montesquieu takes the right direction in conceiving the state as an organic unity, he failed to properly formulate the relation between the political constitution and the division of powers. Thus, Hegel claims that liberal political theories fail to secure political sovereignty, since they consider political constitution to be logically prior and legally superior to political powers. By contrast, Hegel argues that only the constitutional monarchy that functions as a higher unity of the executive and the legislative power can secure a genuine political sovereignty.